2007
DOI: 10.2319/060806-234
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Ligament Hydrostatic Pressure with Areas of Root Resorption after Application of a Continuous Torque Moment

Abstract: Objective: To evaluate the risk of root resorption, individual finite element models (FEMs) of extracted human maxillary first premolars were created, and the distribution of the hydrostatic pressure in the periodontal ligament (PDL) of these models was simulated. Materials and Methods: A continuous lingual torque of 3 Nmm and 6 Nmm respectively was applied in vivo to the aforementioned teeth. After extraction, FEMs of these double-rooted teeth were created based on high-resolution microcomputed tomographics (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
99
1
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(197 citation statements)
references
References 20 publications
6
99
1
9
Order By: Relevance
“…This could be due to the relatively lower torque magnitude used in this experiment (approximately 5 N/mm) that might not be enough to produce contact of the roots of these premolars with their respective cortical plate. 7,10 In our study, increased root resorption was observed at the apical third, followed by the middle third and cervical third. This is likely because torque results in compressive forces being concentrated at the apex, 10,34 which is more susceptible to root resorption.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…This could be due to the relatively lower torque magnitude used in this experiment (approximately 5 N/mm) that might not be enough to produce contact of the roots of these premolars with their respective cortical plate. 7,10 In our study, increased root resorption was observed at the apical third, followed by the middle third and cervical third. This is likely because torque results in compressive forces being concentrated at the apex, 10,34 which is more susceptible to root resorption.…”
Section: Discussionmentioning
confidence: 74%
“…7,10 In our study, increased root resorption was observed at the apical third, followed by the middle third and cervical third. This is likely because torque results in compressive forces being concentrated at the apex, 10,34 which is more susceptible to root resorption. 35,36 Schwarz 37 reported that orthodontic force should not exceed the capillary blood pressure, and areas in which the orthodontic force exceeds the capillary blood pressure show root resorption.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations